Intrinsic subtypes and therapeutic decision-making in hormone receptor-positive/HER2-negative metastatic breast cancer with visceral crisis: A case report - Schettini, Francesco; Seguí, Elia; Conte, Benedetta; Sanfeliu, Esther; Gonzalez-Farre, Blanca; Jares, Pedro; Vidal-Sicart, Sergi; Ganau, Sergi; Cebrecos, Isaac; Brasó-Maristany, Fara; Muñoz, Montserrat; Prat, Aleix; et al. (Frontiers in Oncology, 2022)
Background. CDK4/6-inhibitors (CDKi), namely palbociclib, ribociclib and abemaciclib, combined with either an aromatase inhibitor (AI) or fulvestrant are the standard first/second line for hormone receptor-positive(HR+)/HER2-negative(neg) metastatic breast cancer (MBC). However, the choice of one specific CDKi is arbitrary and based on physician’s experience with the drug, toxicity profile and patient’s preferences, while biomarkers for optimal patient selection have not been established so far. Moreover, upfront chemotherapy is still recommended in case of clinical presentation with visceral crisis, despite no evidence of superior benefit for chemotherapy regimens against CDKi-based regimens. Recent correlative biomarker analyses from pivotal trials of palbociclib and ribociclib showed that HR+/HER2-neg MBC might respond differently according to the molecular intrinsic subtype, with Luminal A and B tumors being sensitive to both CDKi, Basal-like being insensitive to endocrine therapy, irrespective of CDKi, and HER2-enriched tumors showing a benefit only with ribociclib-based therapy. Clinical case. We hereby present a paradigmatic clinical case of a women affected by a relapsed HR+/HER2-neg MBC with bone and nodal lesions, presenting with a visceral crisis in the form of lymphangitis carcinomatosis and diagnosed with a molecularly HER2-enriched tumor, successfully treated with upfront ribociclib + fulvestrant. The patient experienced a complete symptomatic and radiologic remission of the lymphangitis with a partial response as best response, according to RECIST 1.1 criteria. The progression-free survival (PFS) was of 20 months, in line with the median PFS observed in ribociclib + fulvestrant pivotal trial, where, however, patients with visceral crisis had been excluded. Conclusions. This clinical case confirms in the real-world setting that non-Luminal subtypes can be found in HR+/HER2-neg disease and may have potential therapeutic implications in the metastatic setting. It also questions the recommendation of upfront chemotherapy in the case of a visceral crisis in the era of CDKi-based regimens. These issues merit further evaluation in prospective and larger studies.